Rumours of Peace, Whispers of War : Assessment of the Reintegration of Ex-combatants into Civilian Life in North Kivu, South Kivu, and Ituri, Democratic Republic of Congo - Lamb, Guy; Alusala, Nelson; Mthembu-Salter, Gregory; Gasana, Jean-Marie (World Bank, Washington, DC, 2017)
The eastern Democratic Republic of the Congo (DRC) is poised on the edge of a machete blade. Despite the achievement of considerable peace-building successes throughout much of this central African state in recent years, the current activities of armed groups and the Congolese armed forces in North Kivu, South Kivu, and Ituri, have the potential to further destabilize the eastern provinces, and possibly even neighboring countries. Former combatants are prominent in the security and stability equation in the eastern DRC. The reason is that if this section of society has not been effectively disarmed, demobilized and reintegrated into civilian life, then they have the potential to return to arms. In this region, over 100,000 ex-combatants have been demobilized over the past decade in successive waves of disarmament, demobilization and reintegration (DDR) interventions. Assessments and speculation about the reintegration of ex-combatants in North Kivu, South Kivu and Ituri have suggested that these individuals have become marginalized, and their reintegration into civilian society is precarious, thus making them vulnerable to further recruitment by armed groups. Some reports have even suggested that numerous former fighters have remilitarized in the mining areas in order to access mineral wealth. Consequently, research on the socio-economic reintegration of ex-combatants in the eastern DRC was undertaken by the Institute for Security Studies (ISS), and funded by the Transitional Demobilization and Reintegration Program (TDRP) of the World Bank. North Kivu, South Kivu and Ituri were the three geographical areas of focus, given the volatility and potential pivotal role of these areas in promoting and consolidating peace in the eastern DRC. The specific objectives of the research were to: 1) assess the processes of the socio-economic reintegration of former combatants into civilian life; 2) analyze the causes and dynamics of the current security situation (or lack thereof) in the three areas, and the implications for current and future DDR processes; and 3) evaluate the extent to which demobilized former combatants have been re-recruited into armed groups, including motivating and resilience factors. The research took place between February and September 2011, with the findings and analysis being presented in this report.